Population-based studies highlighting the prevalence of sleep-related disorders in adults with respect to ethnicity - Mohamad Noor, Zaswiza; Smith, Alesha; Nissen, Lisa M. (2011)
Introduction: To eliminate disparities in health outcomes due to sleep disorders there is a need to not only focus on social and environmental factors, but also possible biological or genetic differences. This paper highlights studies investigating ethnic prevalence of certain sleep-related disorders in different populations.